Thought-experiment intuitions and truth in fiction. - Ichikawa, Jonathan; Jarvis, Benjamin (Philosophical Studies, 2009)
What sorts of things are the intuitions generated via thought experiment? Timothy Williamson has responded to naturalistic skeptics by arguing that thought-experiment intuitions are judgments of ordinary counterfactuals. On this view, the intuition is naturalistically innocuous, but it has a contingent content and could be known at best a posteriori. We suggest an alternative to Williamson’s account, according to which we apprehend thought-experiment intuitions through our grasp on truth in fiction. On our view, intuitions like the Gettier intuition are necessarily true and knowable a priori. Our view, like Williamson’s, avoids naturalistic skepticism.